2021
DOI: 10.1101/2021.03.24.21253992
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Case Study: Longitudinal immune profiling of a SARS-CoV-2 reinfection in a solid organ transplant recipient

Abstract: Prior to the emergence of antigenically distinct SARS-CoV-2 variants, reinfections were reported infrequently - presumably due to the generation of durable and protective immune responses. However, case reports also suggested that rare, repeated infections may occur as soon as 48 days following initial disease onset. The underlying immunologic deficiencies enabling SARS-CoV-2 reinfections are currently unknown. Here we describe a renal transplant recipient who developed recurrent, symptomatic SARS-CoV-2 infect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 71 publications
(87 reference statements)
0
12
0
Order By: Relevance
“…In total, 35 articles describing the clinical courses of 60 unique individuals were identified that met the criteria. 7 14 , 18 – 43 An additional 114 articles were identified following abstract screening, but were not included in the analysis because they did not have sufficient sequencing results to conclude that the cases were reinfections. In total, 60 cases of verified reinfection were identified in this search.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 35 articles describing the clinical courses of 60 unique individuals were identified that met the criteria. 7 14 , 18 – 43 An additional 114 articles were identified following abstract screening, but were not included in the analysis because they did not have sufficient sequencing results to conclude that the cases were reinfections. In total, 60 cases of verified reinfection were identified in this search.…”
Section: Resultsmentioning
confidence: 99%
“…Then, we extracted the relevant data and organized them in tables. The original papers that were peer-reviewed and published in English and fulfilled the eligibility criteria were included in the final report, together with two works not reviewed at the time of preparation of this report [30,31].…”
Section: Study Selectionmentioning
confidence: 99%
“…This could explain variable performance between two geographically distinct sites (in the Pacific North West of the USA in the study by Drain et al [ 15 ] and Germany). However, this appears very unlikely given the multiple antibodies used in the test that target the nucleocapsid, which is a rather conserved target even in recent strain variants [ 30 ]. While a hook or prozone effect could be considered, it appears unlikely in light of the sample type and has not been shown in prior experiments by the manufacturer [ 12 ].…”
Section: Discussionmentioning
confidence: 99%